Electricity Demand, Supply and Costs - Paškevičius, Vladas; Staškevičjus, Juozapas Audvydas (Ekonomika, 1996)
The economical situation and development of any country depends on the continuous supply of electrical power at favourable prices. When buying fuel at world prices the problem of production cost becomes critical. In Lithuania, the electrical power generating capacity considerably exceeds the demand and without a substantial increase of export it is impossible to enlarge the loading of power stations. When calculating production cost, the wear of equipment must be seriously taken uno account.